ANALISIS MANAJEMEN KAS, PIUTANG DAN PERSEDIAAN TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Sitorus, Dian Dita Mardiana; Br Purba, Neni Marlina (SCIENTIA JOURNAL, 2022)
Profitability is the main goal in establishing a company. Profitability is a ratio that can measure the company's ability to obtain operating profits. This study aims to examine and examine the effect of Cash Management (Cash Ratio), Accounts Receivable (Receivable Turnover) and Inventory (Inventory Turnover) on the Profitability (ROA) of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange. This research is a quantitative research with research data taken in the period of 2016-2020. The total population is 30 companies with a total sample of 7 companies. Sampling is done by using purposive sampling method. Data analysis methods used in this study include multiple linear analysis with partial test hypothesis testing (t test), simultaneous test (f test) and coefficient of determination test carried out with the help of SPSS version 25 program. The results of the analysis show that there is no influence between cash management on profitability where the significant level is 0.071 > 0.05 and the value of Tcount < Ttable (1.868 < 2.0395), accounts receivable has a significant negative effect on profitability with a significant level of 0.032 < 0.05 and the value of Tcount < T table (-2.250 < - 2.0395) , inventory has a significant positive effect on profitability with a significance of 0.000 < 0.005 and the value of Tcount > T table (6.505 > 2.0395). In the results of the f-test of cash management, accounts receivable and inventory simultaneously affect profitability with a significance of 0.000 < 0.005 and the value of Fcount > Ftable (18.137 > 2.9). While the results of the adjusted r-square determination test show that the independent variable is able to explain the dependent variable by 60.2% while the remaining 39.8% is influenced by other variables outside this study.